Understanding of He Hongfang's Prescription (何鸿舫方) - Jin Quan (Wolters Kluwer Health/LWW, 2020)
He Hongfang (何鸿舫), a medical scholar in the Qing Dynasty, was the 24th descendant of He's family in Jiangnan Region. He was famous in Shanghai during the reign of Tongzhi and Guangxu for his medicine and calligraphy. This article introduces two frames of prescriptions of He Hongfang in the Shanghai Museum of Traditional Chinese Medicine for appreciation.